2019
DOI: 10.1108/jmlc-03-2018-0023
|View full text |Cite
|
Sign up to set email alerts
|

Control of fraud on mobile money services in Ghana: an exploratory study

Abstract: Purpose Fraud is a global economic menace which threatens the survival of individuals, firms, industries and economies, and the mobile money service is no exception. This paper aims to explore the main causes of fraud in the mobile money services in Ghana and the measures to combat the menace by the key stakeholders connected to the mobile money services. The paper is motivated by recent reports of numerous fraudulent transactions on the mobile money platform, and the need to clamp down these nefarious transac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 31 publications
1
28
0
1
Order By: Relevance
“…Although, there have been studies on fraud based on various fraud theories (Akomea-Frimpong et al , 2016; Baz et al , 2016a; Reurink, 2016; Said et al , 2017; Muhsin et al , 2018a, 2018b; Akomea-Frimpong et al , 2019; Asmah et al , 2020), the focus had not been on fraud at the executive and management level in banks, especially in the Ghanaian context where “owner CEOs” dominate privately owned banks. In the case of Ghana, few studies focussed on the effect of financial fraud on the financial performance of financial institutions (Akomea-frimpong et al , 2016; Bonsu et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Although, there have been studies on fraud based on various fraud theories (Akomea-Frimpong et al , 2016; Baz et al , 2016a; Reurink, 2016; Said et al , 2017; Muhsin et al , 2018a, 2018b; Akomea-Frimpong et al , 2019; Asmah et al , 2020), the focus had not been on fraud at the executive and management level in banks, especially in the Ghanaian context where “owner CEOs” dominate privately owned banks. In the case of Ghana, few studies focussed on the effect of financial fraud on the financial performance of financial institutions (Akomea-frimpong et al , 2016; Bonsu et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas mobile money has stimulated financial inclusion to lots of unbanked Ghanaians, Togo lags behind in its mobile money acceptance rate. Early studies have investigated consumer adoption of mobile money services in Africa (including Togo) [22][23][24]. However, limited studies have probed the factors that contribute to the continued usage of mobile-based money technology and services within the underbanked and unbanked user segment and beyond.…”
Section: Introductionmentioning
confidence: 99%
“…Spoofing attacks: This attack occurs when the adversary assumes the role of a mobile system administrator and has full access to the system. This is common because most mobile money applications and systems are poorly protected, thus giving opportunity for the attackers to hack them [16,23]. Social engineering attack: This is the manipulation of people to reveal confidential information like mobile money PIN so that the attacker can gain control over the user's mobile money account [19].…”
Section: Attacks Against Authenticationmentioning
confidence: 99%
“…Despite the considerable effort invested in providing a more robust and secure system, most of the existing MMSs still rely on a weak two-factor authentication (2FA) scheme. Various attacks to mobile money's 2FA scheme include man-in-the-middle (MITM) attack, authentication attack, replay attack, identity theft, USSD technology vulnerabilities, brute force attack, social engineering attacks, and denial of service (DoS) attack [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Reaves et al [23] also observed that the current MMS uses nonstandard cryptography, which is easily compromised, thus limiting the integrity and privacy guarantees of the software, giving rise to the threat of forged transactions and loss of transaction privacy.…”
Section: Introductionmentioning
confidence: 99%